User interface design: A study of expectation- confirmation theory - Baharum, Aslina; Jaafar, Azizah (2015)
In a century of high technology and in a cyber world, the website is recognized as a super fast medium of information transfer, sharing and data harmonization.Users around the world look for information in various kinds of websites and online sources.These multicultural users have different experiences and expectations regarding the structure of a website and how to use it. However, there are limited guidelines for the development of websites for multicultural users. In particular, there is a lack of specific standards for user-centric websites that should be taken into account during the development of a website.Such guidelines would be useful in giving designers an overview of how to develop websites that will satisfy the expectations of users around the world.The present study explored ASEAN users’ expectations of an informational website based on expectation-confirmation theory (ECT), which is adapted from the consumer behavior literature. Eight constructs, namely, expectation, perceived usefulness, perceived ease of use, perceived performance, satisfaction, interface quality, confirmation and continuance intention were used to measure a user-centric Web-based interface. The results of the study demonstrate satisfactory reliable and valid scales of the model constructs.